Surface plasmon wave application in microwave modulator induced by switchable metamaterial. Issue 2 (February 2016) - Zhang, Wenjuan; Sun, Liguo; Lin, Fujiang; Zhu, Guiqiang; Lu, Diqun
ABSTRACT: Corrugated metal surface with underlayer metal ground can propagate surface waves when the operation frequency is below the asymptotic limit–the surface plasma frequency. Tunability of the spoof surface plasmon polariton (SSPP) wave is realized by placing metamaterial underneath the SSPP strip. We design and experimentally demonstrate a modulator based on the planar surface plasmon waveguide and switchable metamaterial, where PIN diodes are implemented to tune the metamaterial. With the diodes working in on/off states, the proposed modulator can be, respectively, viewed as a signal‐stop/signal‐pass circuit at the operation frequency. The experimental results validated this method. It is observed that the proposed modulator would operate from 2.51 to 2.57 GHz with 12 dB on‐off isolation. © 2016 Wiley Periodicals, Inc. Microwave Opt Technol Lett 58:261–263, 2016